The Influence of Host miRNA Binding to RNA Within RNA Viruses on Virus Multiplication - Lei, Lin; Cheng, Anchun; Wang, Mingshu; Jia, Renyong (Frontiers in Cellular and Infection Microbiology, 2022)
microRNA (miRNA), non-coding RNAs about 22nt long, regulate post-transcription expression of genes to influence many cellular processes. The expression of host miRNAs is affected by virus invasion, which also affects virus replication. Increasing evidence has demonstrated that miRNA influences RNA virus multiplication by binding directly to the RNA virus genome. Here, the knowledge relating to miRNAs the relationships between host miRNAs and RNA viruses are discussed.